2015
DOI: 10.2147/ndt.s77910
|View full text |Cite
|
Sign up to set email alerts
|

A case-control proton magnetic resonance spectroscopy study confirms cerebellar dysfunction in benign adult familial myoclonic epilepsy

Abstract: BackgroundBenign adult familial myoclonic epilepsy (BAFME) is a rare form of epilepsy syndrome. The pathogenesis of BAFME remains unclear, though it seems to involve dysfunction of the cerebellum.ObjectivesThe purpose of this study was to use proton magnetic resonance spectroscopy (1H-MRS) to investigate whether neurochemical changes underlie abnormal brain function in BAFME.MethodsTwelve BAFME patients from one family and 12 age- and sex-matched healthy controls were enrolled in this study. The ratios of NAA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“… 13 1 H-MR spectroscopy was used to demonstrate prominent cerebellar dysfunction in BAFME. 14 , 15 A diffusion tensor imaging study reported decreased cerebellar fiber density in BAFME, 16 and a case study found fronto-striatal dysfunction in type 3 BAFME during aging using single photon emission computed tomography. 17 It seems that cerebellar atrophy is a convergent finding in BAFME patients.…”
Section: Introductionmentioning
confidence: 99%
“… 13 1 H-MR spectroscopy was used to demonstrate prominent cerebellar dysfunction in BAFME. 14 , 15 A diffusion tensor imaging study reported decreased cerebellar fiber density in BAFME, 16 and a case study found fronto-striatal dysfunction in type 3 BAFME during aging using single photon emission computed tomography. 17 It seems that cerebellar atrophy is a convergent finding in BAFME patients.…”
Section: Introductionmentioning
confidence: 99%
“…- Cerebellar findings include in French pedigrees mild ataxia and gait instability, 17 , 37 , 38 , 62 (downbeat) nystagmus increasing with hyperventilation in a Dutch pedigree, 14 and dysarthria in South African/French pedigrees. 10 , 38 Ataxia is not a feature of FCMTE 16 , 17 , 27 , 47 , 57 , 58 , 60 , 65 but subtle cerebellar signs have not explicitly been ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…Valproate is the drug most often reported to be effective with or without clonazepam. 13 , 16 , 17 , 27 , 43 , 47 , 48 , 56 , 58 , 60 , 65 , 74 Because of teratogenicity, this should not be prescribed to women of childbearing age. Newer AEDs with a good effect are levetiracetam 13 , 17 , 37 , 38 , 43 , 46 , 48 , 58 , 74 , 75 and lamotrigine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations